Cinema and remote teaching: Audiovisual as a possibility of learning in the context of the pandemic - Brito, Luciana Helena da Silva; Silveira, Arlindyane Santos da; Silva, Joseylza Lima (Seven Editora, 2024)
This text derives from the research on the Cine Humanas Teaching Project, an integrative project of IFMA Campus Barra do Corda, executed in remote, synchronous, hybrid and face-to-face forms, with the application of various platforms. Thus, a discussion will be made about the impacts of audiovisual, specifically feature films and short films, within the perspective of active methodologies. The work developed a research of an applied nature, with a qualitative approach. As for the procedures, action research was applied, using as a universe of analysis the students of the integrated technical high school classes of the Buildings, Administration, Informatics and Chemistry courses, of the three years, enrolled in the IFMA Campus Barra do Corda. The objective was to observe the critical positioning of the students because of the exhibition of feature and short films. It was noticed that the semiotic elements used in the films within a plot reinforce the criticality expressed in debates, essays, and texts. DOI:https://doi.org/10.56238/sevened2023.006-117